Perception of Abortion in Indonesian and American Cultures Reflected in Indonesian and American Dramas - Maria Friska T. L. (Compendium: Journal of Cultural, Literacy, and Linguistic Studies, 2017)
The drama "Keely and Du" by Jane Martin and "Abortion" by Subrata Kalape are the representation of life. Although the dramas talk about abortion, they represent a different message. This paper aims to discuss the different perceptions of abortion based on both dramas. The authors used a qualitative approach and a comparative study to compare the contents and dialogues between the two dramas. The result of this study shows the different perception of abortion in America and Indonesia. This finding indicates that cross cultural understanding is important to understand the cultural differences in America and Indonesia. Keyword: Drama, Abortion, Culture, Perception, America, Indonesia